2017
DOI: 10.18632/oncotarget.21738
|View full text |Cite
|
Sign up to set email alerts
|

MP0250, a VEGF and HGF neutralizing DARPin® molecule shows high anti-tumor efficacy in mouse xenograft and patient-derived tumor models

Abstract: BackgroundThe VEGF/VEGFR and the HGF/cMET pathways are key mediators of the interplay of tumor cells and their microenvironment. However, inhibition of VEGF has been shown to produce only limited clinical benefit and inhibition of the activation of cMET by HGF has not translated into clinical benefit in pivotal trials. MP0250, a DARPin® molecule that specifically inhibits both VEGF and HGF has been developed to explore the clinical potential of dual inhibition of these pathways.ResultsMP0250 binding to VEGF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
(55 reference statements)
0
24
1
Order By: Relevance
“…Its pharmacokinetic profile and pharmacologic activity make MP0250 a promising candidate for cancer therapy. Fiedler et al 25 have shown efficacy of MP0250 in a number of mouse tumor xenograft models, indicating that the drug candidate indeed has the potential to improve patient benefit beyond single agent anti-VEGF therapy. Based on the results shown here, the preclinical in vivo data, as well as safety and tolerability assessments, clinical testing of MP0250 has been initiated (ClinicalTrials.gov Identifier NCT02194426).…”
Section: Discussionmentioning
confidence: 99%
“…Its pharmacokinetic profile and pharmacologic activity make MP0250 a promising candidate for cancer therapy. Fiedler et al 25 have shown efficacy of MP0250 in a number of mouse tumor xenograft models, indicating that the drug candidate indeed has the potential to improve patient benefit beyond single agent anti-VEGF therapy. Based on the results shown here, the preclinical in vivo data, as well as safety and tolerability assessments, clinical testing of MP0250 has been initiated (ClinicalTrials.gov Identifier NCT02194426).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Abs against anti-angiopoietin-2 (like nesvacumab, AMG780, MEI3617, and vanucizumab), and Abs anti-integrin αvβ3 have been successfully tested in phase I/II study [40,41]. Another example of an antibody targeting alternative angiogenic pathways is MP0250, a genetically engineered designed ankyrin repeat protein (DARPin ® ) that specifically binds to VEGF-A, hepatocyte growth factor (HGF), and human serum albumin (HSA) [42,43]. The antibody is currently being studied in phase I and II clinical trials on multiple myeloma relapses (NIH N. NCT03136653) [44] on EGFR-mutated non-small cell lung cancer (NIH N. NCT03418532) and on other neoplasms (NIH N. NCT02194426).…”
Section: Alternative Anti-angiogenic Antibodiesmentioning
confidence: 99%
“…A phase 1 study [ 37 ] showed a good safety profile and some activity in patients with c-Met abnormalities. MP0250 is a dual-specific antibody mimetic (a designed ankyrin repeat protein (DARPin ® ) that functions as a neutralizing protein for both VEGF and HGF [ 75 ]. It contains two human serum albumin antibody mimic sequences that flank an anti-HGF and an anti-VEGF sequence, producing a moiety that binds and neutralizes both VEGF and HGF [ 75 ].…”
Section: Biological Antagonists Of Hgf or C-metmentioning
confidence: 99%